(Un)spoken: The register and display of the artist's voice in the museum. Issue 1 (2nd January 2016) - Ross, Alexandra
ABSTRACT: This article is a two-fold exploration of the voice in relation to the documentation of artistic practice, whilst also focusing on the nuance and agency of the voice, its capture and presentation. Particularly in connection to the museum, this article posits the potential of approaching contemporary artworks displayed in a museum in an expanded and polyphonic manner. Drawing from a lineage of artistic example, it considers the possibilities and limitations of working with the voice and how to record and represent the interstitial, intimate or informal spaces of artistic production. The role of the museum as safeguard and mediator of artwork has been evolving apace to also accommodate the transparency of process, thus allowing for the revealing of institutional and artistic processes. With this reveal comes an enhanced understanding of the context in which an artwork was created and subsequently how it came to find itself within a particular collection.